Kegiatan Parenting Orang Tua Terhadap Anak Di Era New Normal Di Kabupaten Pasaman Barat - Tria Citra; Asdi Wirman (Universitas Negeri Padang, 2021)
The spread of Covid-19 has an impact on learning activities in schools. Therefore, this study aims to provide an overview of how parenting activities are carried out by parents for early childhood during the new normal period. Parents have different characteristics that affect the parenting applied and they are just adapting to the current state of the Covid-19 pandemic. This research uses descriptive quantitative method. The sampling technique used was non-probability sampling, data was collected using questionnaires and analyzed using descriptive statistics. Parenting activities carried out in the new normal period were carried out as usual activities but accompanied by new normal habits by implementing health protocols. Based on the research results, parents' answers on average rarely, sometimes and often implement new normal parenting activities. Parents who answered rarely worked as housewives because they were still indifferent to health protocols and thought that parenting activities had been carried out by teachers at schools. While sometimes and rarely are working parents such as civil servants, entrepreneurs and private employees, this is mostly due to the busy work of parents, but there are also some parents who have often implemented new normal parenting on the sidelines of their busy lives